ESTETIKA VISUAL KORIDOR PADA BANGUNAN-BANGUNAN KOMERSIL DI JALAN PANDANARAN SEMARANG - Mutiawati Mandaka (Universitas Pandanaran, 2015)
Semarang, as a big city, has rapidly developed in buildings. It is indicated mainly by the increasing number of commercial buildings such as supermarkets, office buildings and mall. It also occurred on Pandanaran street, where buildings use for housings become commercial buildings. Signage is needed to give the identity of building which is used as communication tool in architecture and direct information for community. Based on function, there are four reason why signage is needed in a city : traffic sign, commercial identity, informational sign and mall identity. In fact, on Pandanaran street, signage is dominated by commercial identity. Besides the trespassing line, the commercial corridor has developing to be the media for expressing and giving information, because advertising is the effective way to win the market competition. This research is aimed to find the influence of signage to visual aesthetic corridor on Pandanaran street in Semarang. Based on literature and existing condition, the elements that construct the character of visual corridor are façade the typhology of space and its activity.Keyword: urban design, signage, visual corridor, aesthetic